Adolescent Mental Health Interventions: A Review of Psychological and an Islamic Approach - Samsiah binti Mohd Jais, Mohammad Aziz Shah bin Mohamed Arip (Tanjung Malim, 2024)
Adolescent Mental Health Interventions: A Review of Psychological and an Islamic Approach by Samsiah binti Mohd Jais, Mohammad Aziz Shah bin Mohamed Arip